2010
DOI: 10.1002/jbm.b.31767
|View full text |Cite
|
Sign up to set email alerts
|

The effect of betacyclodextrin and hydroxypropyl betacyclodextrin incorporation into plasticized poly(vinyl chloride) on its compatibility with human U937 cells

Abstract: Di (2-ethyl hexyl) phthalate (DEHP) is one of the main plasticizers used in poly(vinyl chloride) (PVC) medical devices and is currently the only one listed for use in the European Pharmacopoeia Monograph. It leaches out of PVC when the material is in contact with lipophilic media, for example, blood and certain nutritional feeds. Consequently, concerns have been expressed since in certain animal species, DEHP has been shown to exhibit both carcinogenic and reproductive toxic effects. Incorporation of beta cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Zimmer et al [ 49 ] reported anti-inflammatory effects of HPβCD in vivo in a mice model of atherosclerosis. At the cellular level, George et al [ 56 ] assumed an anti-inflammatory property of HPβCD after showing that its presence along with plasticized poly(vinyl chloride) (PVC) reduced LPS-induced TNF-α expression in human monocyte-like U937 cells while PVC alone had no effect. Matassoli et al [ 57 ] showed that HPβCD can inhibit LPS-induced TNF-α secretion in primary human monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Zimmer et al [ 49 ] reported anti-inflammatory effects of HPβCD in vivo in a mice model of atherosclerosis. At the cellular level, George et al [ 56 ] assumed an anti-inflammatory property of HPβCD after showing that its presence along with plasticized poly(vinyl chloride) (PVC) reduced LPS-induced TNF-α expression in human monocyte-like U937 cells while PVC alone had no effect. Matassoli et al [ 57 ] showed that HPβCD can inhibit LPS-induced TNF-α secretion in primary human monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclodextrins are cyclic oligosaccharides commonly composed of six, seven, and eight α‐ d ‐glucose units (α‐,β‐, and γ‐CD, respectively) that have a shape like a truncated cone . They have a hydrophobic interior that is capable of encapsulating of poorly water‐soluble molecules completely or partially in aqueous environment .…”
Section: Introductionmentioning
confidence: 99%